A new approach to collaborative creativity support of new product designers. (1st January 2011) - Bitter-Rijpkema, Marlies; Sloep, Peter B.; Sie, Rory; van Rosmalen, Peter; Retalis, Symeon; Katsamani, Mary
Effective collaborative creativity is crucial to contemporary professionals who have to continuously produce innovative products and services. The technological nature and complexity of the innovations require team work, among specialists from different disciplines. Often these teams work in a distributed fashion, across boundaries of time and place. Therefore, they need electronic 'spaces' that support ('afford') their creative collaboration. Co-creativity support is not only a matter of making appropriate groupware spaces available but also of providing concurrent support in all these dimensions. These considerations inspired the development of the idSpace platform. idSpace is a collaboration platform integrating a variety of creativity tools with pedagogy-based guidance. It aims to optimise both the use of creativity techniques themselves and of the supporting processes of team collaboration and knowledge creation. In this paper, we zoom in on knowledge-sharing strategies for collaborative creativity (KS4CC). We show how collaborative creativity can be enhanced via integration of pattern-based pedagogical flow support, including suggestions of optimal use of creativity techniques. The KS4CC strategies consist of a merger of learning and collaboration flow patterns with support for the application of creative techniques.